Influência do ácido zoledrônico na progressão de periodontite apical em ratas com osteoporose e associação do estresse oxidativo com conteúdo mineral ósseo - Bello, Mariana De Carlo (2017)
The present thesis was structured in two studies presented as two articles, that investigated the association between the parameters of Oxidative Stress (OS) and osteoporosis and the systemic and local effects of the osteoporosis treatment with Zoledronic Acid (ZOL). The first paper evaluated the association between OS markers and Bone Mmineral Content (BMC) of the femur, as well as determined the presence of these markers in the liver of rats with osteoporosis treated and untreated with ZOL. Wistar rats were divided into 4 groups (n = 10): OVX - ovariectomy surgery and vehicle treatment; OVX + ZOL - ovariectomy surgery and ZOL treatment; SHAM - sham surgery and vehicle treatment; SHAM + ZOL - sham surgery and ZOL treatment. Twenty-one days after surgery, vehicle or ZOL were administered in a single application. After 35 days the animals were euthanized. Oxidative damage and antioxidant defenses in the liver were evaluated by measuring the levels of Lipid Peroxidation (LP), Reactive Oxygen Species (ROS), Nitric Oxide (NOx), non-protein thiol groups and vitamin C. From multivariate regression it was observed that markers of oxidative damage (LP, ROS, NOx) were associated with reduction of BMC in both cancellous and cortical bone (P < .05). In the adjusted analysis, ROS and ZOL presented negative and positive association, respectively, with BMC in both cancellous and cortical bone (P < .05). It was concluded that OS markers were associated with the occurrence of osteoporosis and ZOL treatment helps in maintaining bone mass. The second paper evaluated the influence of a single dose of ZOL on the size of Periapical Lesions (PL) in ovariectomized and control rats; additionally, it was evaluated systemic parameters such as ROS, white blood cell count and BMC in the femur and mandible. The second paper used the same groups described above. Twenty-one days after surgery, pulp exposure of the first right mandibular molar of all animals was performed in order to induce apical periodontitis. On the same day, vehicle or ZOL was administered in a single application. After 35 days, the PL area was measured by histometric analysis. Local and systemic inflammatory infiltrate were evaluated by histological and hematological analyses, respectively. ROS levels were quantified to estimate oxidative damage. It was observed that the PL size was similar between the groups (P > .05). Local and systemic inflammatory infiltrate were not affected by treatment with ZOL (P > .05). The OVX and OVX + ZOL groups presented higher levels of ROS than SHAM groups (P < .05). ZOL decreased ROS levels in ovariectomized rats (P < .05). It was concluded that ZOL therapy does not interfere in the periapical bone loss and in the inflammatory parameters. However, ZOL reduced a marker of oxidative damage.